Analysis of Allocation of Village Funds through the Establishment of Village-Owned Enterprises (BUMDES ) According to an Islamic Economic Perspective (Case Study of Bumdes in Lampung Province) - Suhendar Suhendar; Ruslan Abdul Ghofur; Fatih Fuadi (International Journal of Educational Research Excellence (IJERE), 2023)
is research aims to analyze the Allocation of Village Funds through the Establishment of Village-Owned Enterprises (Bumdes) according to an Islamic Economic Perspective (Case Study of Bumdes in Lampung Province). The method used in this research is a descriptive method with a qualitative approach. Research procedures are an explanation of the steps that must be taken in a study. The research procedure steps include three things, namely observation, interviews and documentation. The data analysis technique used in this research is interactive analysis. This model has four analytical components, namely: data collection, data reduction, data presentation, and drawing conclusions. The results of this research explain 1) All regencies/cities in Lampung Province have allocated an average of 10% of Village Funds to BumDes. This shows that the village government is serious in supporting the role of Bumdes to increase the economic growth of society in Lampung Province, and 2) Economic growth must be based on the values of faith, piety, and consistency and perseverance to let go of all the values of immorality and sin. This does not deny the existence of efforts and thoughts to catch up with all backwardness and underdevelopment in accordance with sharia principles.